PROPOSED STRATEGY OF BIODIESEL FUEL POLICY IN THE COAL MINING INDUSTRY - A CASE STUDY OF PT. BERAU COAL (The Indonesian Journal of Business Administration, 2020)
The mandatory use of biodiesel began in September 2018 and is already widely implemented. Until now, the level of biodiesel blending has reached a level of 30% (B30). In its application to the business activities of PT. Berau Coal, biodiesel, causes several detrimental impacts up to 7.7 million US $ per year. From the results of the root cause analysis, the impact that occurs cannot be separated from the characteristics of the biodiesel itself, the readiness of the Company's infrastructure (filtration system), and weak administrative controls as a result of differences in fuel quality standards between regulations and industrial needs. In connection with these factors, the recommendation proposed is to make comprehensive improvements involving all parties involved in the fuel supply chain process, namely: the government, suppliers, Berau Coal, and mining contractors. Keywords: Biodiesel, Fuel Filtration System, Supply Chain Improvement